Physical activity as a prescription for the children with cerebral palsy - Shariat, Arghavan; Shariat, Ardalan; Ahmad Abedi,; Mohd Tamrin, Shamsul Bahri (Science and Innovation, 2014)
After so many years devoted to practicing medicine as children physiotherapists, the therapists finally found the importance of balance training exercises in children who suffer from cerebral palsy. It is only through controlling balance that we can achieve improvement in body movement and position that will culminate into performance independence in a child. Formerly, working over controlling balance in cerebral palsy children has been very difficult, because contracture and spasticity did not let us to have an effective balance training exercise. In this respect, we have summarized the results of previous authors that specify the level of effectiveness of exercise therapy. The results of different studies showed that level of effectiveness of exercise therapy on alleviating the symptoms of spastic cerebral palsy is average in accordance with Cohen's effect size Interpretation table.